Electronic properties of CaF2 bulk and interfaces - Yuzheng Guo (Journal of Applied Physics, 2022)
The electronic band structures of ultra-wide gap CaF2 are investigated with both the hybrid functional and the efficient generalized gradient approximation (GGA) + U scheme. The hybrid functional scheme is in excellent agreement with experiments, while introducing an on-site Coulomb interaction to F-2p orbitals also accurately reproduces the experimental bandgap and greatly improves the previous theoretical results using advanced electronic structure schemes. We also apply the GGA + U method to study CaF2/Si and metal/CaF2 interfaces. The CaF2/Si insulating interfaces with a clear bandgap are built based on the electron counting rule. Our supercell calculations of the CaF2/Si interfaces show a type-II band alignment and the valence band offset follows a descending trend from (001) to (111) then to (110). The calculation convergence of GGA + U is further tested with the metallic contacts. The metal/CaF2 interfaces are observed to be weakly pinned and different orientations of CaF2 sharing a similar pinning factor S up to ∼0.9, owing to the highly ionic nature of CaF2. The GGA + U approach is proven to be a useful tool in studying such fluoride interfaces and contacts.